Legal Protection for Hajj Pilgrims Through Regional Regulation (UINSI Samarinda, 2018)
The Law on the Conduct of Hajj Pilgrimage mandates the management of the Hajj pilgrimage is organized by the government. This management includes the coaching, service, and protection of the pilgrims from Indonesia, in Saudi Arabia, to returning to the homeland. This law also stipulates that the authority to conduct Hajj pilgrimage management is not only vested to the Ministry of Religious Affairs but also may involve the local government. This article aims to look at the role of local governments in providing service assistance and legal protection to the conduct of Hajj pilgrimage by means of regional regulations or bylaws. Using a normative approach, this article analyzes the extent to which the importance of bylaws in helping implement services for pilgrims. The results of this study confirm that there are 3 important arguments for why the local government must issue regional regulations to provide legal services and protection for pilgrims. First, philosophically, the pilgrimage journey does not depart from Jakarta only, but through the origin area which is still in the corridors of power of the local government. Second, sociologically, it is a form of the local government responsibility to the local people who perform the Hajj pilgrimage. Third, juridically, bylaws should regulate technical matters in order to provide optimal service in the conduct of the Hajj pilgrimage which is pursuant to the Law and regulations on Hajj pilgrimage in Indonesia.Keywords: legal protection, hajj pilgrims, regional regulation.